Dynamics of human defensin 5 (HD5) self-assembly in solution: Molecular simulations/insights. (December 2019) - Chairatana, Phoom; Niramitranon, Jitti; Pongprayoon, Prapasiri
Graphical abstract: Highlights: Dimer is more stable than tetramer in solution. The large oligomeric state is stably form under high salt concentration. E14 residue is essential for the structural integrity, whereas the E21 residue contributes to the dimerization of HD5. Abstract: Human α -defensin 5 (HD5) is a 32-residue cysteine-rich host-defense peptide that exhibits broad-spectrum antimicrobial activity and plays an essential role in innate immunity in the human gut and other organ systems. Although its antimicrobial mechanism of action remains unclear, the high salt concentration seems to attenuate the antimicrobial function of HD5 via an unknown mechanism. In this work, we employ Molecular Dynamics (MD) simulations to analyse the oligomerization behaviour of HD5 when exposed to different salt concentration. We demonstrate that the presence of salt, such as sodium chloride (NaCl), promotes HD5 to form higher-order oligomers (up to heptamers) in our simulations. In addition, we also analyse the electrostatic interactions between the two Glu residues (E14 and E21) and their neighbouring residues. Our data confirm that the E14 residue is essential for the structural integrity, whereas the E21 residue contributes to the dimerization of HD5, suggesting that these Glu residues are important for the antimicrobial function of this peptide.